Penilaian Hasil Belajar Biologi di Bidang Pendidikan - Rahmi, Sagita Nea; Megawati, Megawati; Alberida, Heffi; Fadilah, Muhyiatul (Universitas Negeri Jakarta, 2025)
Learning outcomes assessment is a crucial aspect in determining the effectiveness of a curriculum or teaching process. However, approaches to assessment in the education system often raise questions about the efficiency of various assessments systematically reviewed in the literature on biology learning outcomes assessment in education by analyzing 36 articles from the Scopus database between 2018 and 2023 using the PRISMA approach. The main focus of this review study was to evaluate the most effective assessment methods, as well as further identify the challenges educators face in assessment and understand the implications of changing assessment methods for biology education. Through analyzing data using VOSviewer software, this study revealed trends in the use of technology in assessment, prevalent assessment methods such as formative assessment, and key challenges such as the complexity of biological concepts and technology integration. The results showed the dominance of formative assessment and a shift towards technology in assessment, which emphasizes developing critical thinking skills, scientific reasoning, and inquiry skills. In addition, the study highlighted an increased focus on equity, diversity, and inclusion in assessment practices and the impact of the adoption of distance and online learning on assessment practices.